Surgical Technique: Medial Ulnar Collateral Ligament Reconstruction Using Hamstring Allograft - Hurt, James A. (JBJS Essent Surg Tech, 2013)
INTRODUCTION: In the overhead throwing athlete, medial ulnar collateral ligament reconstruction utilizing a hamstring allograft as an alternative to an autograft provides similar results without the donor site morbidity or potential complications of autograft harvest. STEP 1: MRI OR MRA AND PREOPERATIVE PLANNING: Obtain an MRI or MRA to determine the location and importance of the tear in the ligament. [Figure: see text] STEP 2: MEDIAL ELBOW DISSECTION AND IDENTIFICATION OF THE MEDIAL ULNAR COLLATERAL LIGAMENT: Position the elbow to allow access to the medial side, and expose the medial ulnar collateral ligament via a flexor-pronator split approach. [Figure: see text] STEP 3: PREPARATION OF HAMSTRING ALLOGRAFT: Prepare the non-irradiated hamstring allograft by placing lead Krackow stitches into each end, and if necessary suture it in the middle to help with passage through the bone tunnels. STEP 4: ULNAR-SIDED RECONSTRUCTION: Use a single-hole technique, inserting a Beath pin into the sublime tubercle to allow a single screw to fix the graft into the ulna, OR use a double-hole technique, making connecting drill holes under the sublime tubercle and passing the graft through the tunnels. [Figure: see text] STEP 5: HUMERAL-SIDED RECONSTRUCTION: Place a single drill hole into the center of the origin of the medial ulnar collateral ligament at the distal end of the medial epicondyle; place two connecting tunnels and shuttle the graft ends through these tunnels. [Figure: see text] STEP 6: GRAFT FIXATION AND LIGAMENT REPAIR: Tension the graft while the elbow is placed though a full arc of motion, suture the two limbs of the graft together, and suture the medial ulnar collateral ligament to the graft. [Figure: see text] STEP 7: CLOSURE: Irrigate the wound, repair the flexor-pronator fascia with absorbable suture, and perform a standard subcutaneous and skin closure. RESULTS: Medial ulnar collateral ligament reconstruction utilizing a hamstring allograft instead of an autograft has so far produced excellent results. Indications Contraindications Pitfalls & Challenges